Pengelolaan Limbah Jantung Pisang Menjadi Keripik di Desa Melati II, Pasar 6, Dusun Pala, Kecamatan Perbaungan - Dinda Ameliya; Geby Fatmawati; Mawaddah Syafitri Lubis; Priska Amalia Sipayung; T. Khairani Nada Syavah Harumy (Lembaga Pengembangan Kinerja Dosen, 2026)
Banana blossoms are often considered waste and rarely utilized by the community, even though this material is easily obtained, has nutritional value, and has the potential to be processed into economically valuable food products. This community service activity was carried out in Melati II Village, Pasar 6, Pala Hamlet, Perbaungan District, with the aim of providing assistance to the community in processing banana blossoms into chips as an alternative snack. The implementation method included a brief counseling on the potential and benefits of banana blossoms, training in processing techniques, hands-on practice in making chips, and a simple evaluation of the quality of the resulting product. The results of the activity showed that the community was able to process banana blossoms into chips with a crispy texture, acceptable taste, and an attractive appearance. In addition to improving community skills and creativity, this activity also helped reduce organic waste and opened up sustainable household-scale business opportunities for the local community.